Epstein-Barr Virus (EBV)-positive Sporadic Burkitt Lymphoma. (February 2015) - Satou, Akira; Asano, Naoko; Nakazawa, Atsuko; Osumi, Tomoo; Tsurusawa, Masahito; Ishiguro, Atsushi; Elsayed, Ahmed Ali; Nakamura, Naoya; Ohshima, Koichi; Kinoshita, Tomohiro; Nakamura, Shigeo
<x xml:space="preserve">Abstract</x> Epstein-Barr virus (EBV) is detected in 20% to 30% of sporadic Burkitt lymphoma (sBL). However, only a few studies of EBV-positive (EBV+) sBL have been reported, and its characteristics still remain controversial. To highlight the features of EBV+ sBL, we compared the clinicopathologic characteristics of 33 cases of EBV+ and 117 cases of EBV-negative (EBV−) sBL in Japan. EBV+ sBL showed significantly higher age distribution (median, 42 vs. 13 y; P<0.0001) and higher frequency of patients older than 50 years (48% vs. 16%, P<0.0001). We also revealed the difference of the involved sites. The EBV+ group showed significantly higher incidence of involvement of tonsil (P=0.027), adrenal gland (P=0.011), and cervical lymph node (P=0.040). In addition, the EBV+ group tended to have higher incidence of nodal involvement (P=0.078) and involvement of para-aorta lymph node (P=0.084) and heart (P=0.050). In contrast, the gastrointestinal tract was less frequently affected in EBV+ sBL (P=0.024). In addition, the less positivity for MUM1 (P=0.020) of EBV+ sBL was highlighted. These results indicate that biological behavior and pathogenesis of EBV+ sBL might be different from those of EBV− sBL. Our results demonstrate that EBV+ sBL has an aspect of age-related disease and is a distinct clinicopathologic subtype, which should be distinguished from EBV− sBL.